Feminism and Emotion: Love and the Couple in the Magazine Effe (1973-1982). (1st November 2013) - Morris, Penelope
Abstract : Drawing on recent scholarship on the history of emotions and on feminism in Italy, the article analyses the Italian feminist magazine Effe (1973-1982) and its attempt to rethink notions of love and affective relationships between couples. Whilst a reclaiming of emotions and a re-envisioning of female sexuality were central to 1970s feminism in Italy, Effe was unusual in identifying love — as abstract notion, but also as fact of daily life, both heterosexual and homosexual — as an issue to be addressed in its pages. The article argues that the magazine, influenced in particular by the ideas of American feminist Shulamith Firestone, presents a clear rejection of traditional romantic love, as intimately bound up with the subjugation of women, but that, perplexed by the continuing hold love apparently had over women, and also drawn to an ideal, indeed utopian, vision of love, largely exclusive to women, it is highly ambiguous in proposing an alternative.